2013
DOI: 10.1002/ajhb.22475
|View full text |Cite
|
Sign up to set email alerts
|

Associations between insulin and heart rate variability in police officers

Abstract: Objective Low heart rate variability (HRV) has been linked to cardiovascular disease. Our objective was to examine the cross-sectional association between insulin and HRV. Methods Insulin levels were measured in 355 nondiabetic officers from the BCOPS study, following a 12 h fast. HRV was performed according to methods published by the task force of the European Society of Cardiology and the North American Society of Pacing Electrophysiology for measurement and analysis of HRV. Mean values of high (HF) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
3
15
0
1
Order By: Relevance
“…A similar association was reported in a study from our research group in which participants with metabolic syndrome had elevated blood glucose levels associated with reduced parasympathetic modulation [14]. Also in this perspective, insulin was inversely associated with HRV among patients with higher levels of obesity and lower levels of PA [28], since the severely obese in the present study showed a low amount of minutes spent on MVPA (98.92 ± 41.00 min/week).…”
Section: Discussionsupporting
confidence: 91%
“…A similar association was reported in a study from our research group in which participants with metabolic syndrome had elevated blood glucose levels associated with reduced parasympathetic modulation [14]. Also in this perspective, insulin was inversely associated with HRV among patients with higher levels of obesity and lower levels of PA [28], since the severely obese in the present study showed a low amount of minutes spent on MVPA (98.92 ± 41.00 min/week).…”
Section: Discussionsupporting
confidence: 91%
“…type II diabetes, metabolic syndrome, obesity) also had lower VO 2peak and HR peak [48][49][50]. Recent studies [51,52] have shown that increased insulin and leptin levels are known to adversely affect autonomic nervous system function. High levels of leptin have been shown to be associated with decreased cardiac tone, and hyperinsulinemia to be associated with lower levels of heart rate variability [53,54].…”
Section: Discussionmentioning
confidence: 93%
“…Charles et al recently found that insulin levels were inversely and significantly associated with both HF and LF HRV, although only among those with higher levels of obesity and lower levels of physical activity 34 . Future studies is needed to assess this relationship.…”
Section: Linear Analysis On Hrv and Glycemic Controlmentioning
confidence: 99%